Pancreatitis aguda. Diagnóstico y enfrentamiento inicial en la práctica clínica - Uribe V, Navor; Berger F, Zoltán (Revista Hospital Clínico Universidad de Chile, 2021)
Acute pancreatitis is a prevalent disease, with variable clinical course: several patients recover quickly and uneventfully, while others require treatment in critical care units with long hospital stay and even with a considerable mortality. The patient’s symptoms, laboratory tests and radiological images allow diagnosis without major difficulties. However, early identification of more severe cases can be difficult, and it determines the adequate selection of the hospitalization unit and the quick initiation of the appropriate therapy. In this paper we give some practical treatment guidelines for the everyday clinical practice: immediate severity stratification, fluid replacement and pain control. Early enteral nutrition, monitorization of severe cases in critical care units, adequate therapeutic but no prophylactic use of antibiotics assures the best treatment results.